Investigating form and content of emotional and non-emotional laughing. (9th September 2022) - Lombardi, Giada; Gerbella, Marzio; Marchi, Massimo; Sciutti, Alessandra; Rizzolatti, Giacomo; Di Cesare, Giuseppe
Abstract: As cold actions (i.e. actions devoid of an emotional content), also emotions are expressed with different vitality forms. For example, when an individual experiences a positive emotion, such as laughing as expression of happiness, this emotion can be conveyed to others by different intensities of face expressions and body postures. In the present study, we investigated whether the observation of emotions, expressed with different vitality forms, activates the same neural structures as those involved in cold action vitality forms processing. To this purpose, we carried out a functional magnetic resonance imaging study in which participants were tested in 2 conditions: emotional and non-emotional laughing both conveying different vitality forms. There are 3 main results. First, the observation of emotional and non-emotional laughing conveying different vitality forms activates the insula. Second, the observation of emotional laughing activates a series of subcortical structures known to be related to emotions. Furthermore, a region of interest analysis carried out in these structures reveals a significant modulation of the blood-oxygen-leveldependent (BOLD) signal during the processing of different vitality forms exclusively in the right amygdala, right anterior thalamus/hypothalamus, and periaqueductal gray. Third, in a subsequent electromyography study, we found a correlation between the zygomatic muscles activity and BOLD signal in the right amygdala only.